THE IMPLEMENTATION OF THE SCAFFOLDING METHOD USING THE CONCRETE-PICTORIAL-ABSTRACT (CPA) APPROACH TO ENHANCE MATHEMATICAL CONCEPTUAL MASTERY AMONG GRADE V STUDENTS AT GLR CHRISTIAN ELEMENTARY SCHOOL SURABAYA - Silvia de Fretes; Saparso; Takim Andriono; Maya Devi Kusumadjaja (International Journal of Teaching and Learning, 2025)
This study aims to improve the mastery of mathematical concepts among grade V elementary school students through the implementation of the scaffolding method combined with the Concrete-Pictorial-Abstract (CPA) approach. The research employs a Classroom Action Research (CAR) design, consisting of two cycles. Each cycle includes four stages: planning, action implementation, observation, and reflection. Data were collected through tests, observations, reflections, and interviews. Data analysis was conducted using a combination of quantitative and qualitative methods. The results of the study indicate an improvement in students' conceptual mastery of mathematics. Test scores increased from 73.9% in the pre-cycle to 86.9% in the first cycle, and further to 100% in the second cycle. Analysis of observation sheets, reflections, and interviews showed improvements in all measured indicators from the first to the second cycle: (1) the percentage of students able to restate concepts increased from 90% to 100%; (2) the ability to distinguish between objects reached 100%; (3) the ability to visualize concepts rose from 80% to 100%; (4) students’ ability to follow procedures reached 100%; and (5) the ability to apply learned concepts to solve problems improved from 60% to 80%.